2015
DOI: 10.1134/s1063784215080228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual pressure and ion implantation on the structure, elemental composition, and properties of (TiZrAlYNb)N nitrides

Abstract: Abstract-The nitrides of high entropy alloys, (TiZrAlYNb)N, fabricated by cathodic vacuum arc evapora tion are studied with electron microscopy, atomic force microscopy, laser scanning microscopy; energy dis persive X ray analysis, X ray phase analysis, time of flight secondary ion mass spectrometry; and hardness measurements. It is found that the deposition parameters influence the structure, surface morphology, ele ment distribution, and mechanical properties. The structural-phase state of the coatings befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…These studies have also reported high wear resistance [9], scratch resistance [10] and thermal phase stability [11]. While a significant majority of HEN coatings are produced by magnetron sputtering [8][9][10][11][12][13], a limited number of studies have investigated the use of cathodic arc evaporation to deposit HEN coatings, including those on (TiZrNbAlYCr)N [14], (TiZrHfVNbTa)N [15], (TiZrA-lYNb)N [16] and (MoNbTaVW)N [17]. Compared to magnetron sputtering which has a lower ion flux and ion energy, in CAE the high current density of the arc discharge produces a plasma with high ion flux and ion energy, which improves the coatings' structure and properties [18].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have also reported high wear resistance [9], scratch resistance [10] and thermal phase stability [11]. While a significant majority of HEN coatings are produced by magnetron sputtering [8][9][10][11][12][13], a limited number of studies have investigated the use of cathodic arc evaporation to deposit HEN coatings, including those on (TiZrNbAlYCr)N [14], (TiZrHfVNbTa)N [15], (TiZrA-lYNb)N [16] and (MoNbTaVW)N [17]. Compared to magnetron sputtering which has a lower ion flux and ion energy, in CAE the high current density of the arc discharge produces a plasma with high ion flux and ion energy, which improves the coatings' structure and properties [18].…”
Section: Introductionmentioning
confidence: 99%
“…To date, HENs are predominantly produced as thin films [19][20][21][22][23][24][25] , due to their enhanced solubility and phase stability 26 compared to bulk ceramics. Jin et al 27 reported the synthesis of powdered metal HEN V 0.2 Cr 0.2 Nb 0.2 Mo 0.2 Zr 0.2 N 1−x by planetary ball milling a mixture of five transition-metal chlorides with urea and subsequent annealing of the reactive mixture under N 2 flow.…”
mentioning
confidence: 99%
“…Compounds of this type have a high melting temperature, therefore their synthesis in a film state is performed by magnetron sputtering (RF and DC). At the same time, synthesis features of transition metal nitrides and carbides film materials are manifested in dependence of the formed structure and properties on the incident ions energy and the substrate temperature which leads to the formation of film condensates of different structural statesamorphous, cluster, or nanocrystalline [1,2].…”
Section: Introductionmentioning
confidence: 99%